Introduction : « La Duchesse d’Amalfi, des humeurs baroques à une passion moderne ? » - Gisèle Venet (Sillages Critiques)
Webster’s tragedy, The Duchess of Malfi (1613), shows the weight of the fourteen-century-old Greek conception of compelling passions motivated by « humours », especially the black humour or melancholy. It stages a world still binding together human motivations and the material elements constituting the Cosmos. The black humour determines the actions and passions of the Cardinal and Duke Ferdinand, brothers of the Duchess. It does so all the more as they seek to prevent their sister, a young widow, from wedding again, by hiring an “intelligencer” or spy who is himself prone to the same distemper. Bosola qualifies indeed as a malcontent or a machiavel, two popular figures of the English stage motivated by melancholy. Webster uses his stage to dissect the pathologically perverse and dominating brothers as in a « Barber-Chirurgeon's-hall », with Bosola as the actor and stage-manager of their passions. Away from this dark world of melancholy humours, the Duchess’s bold courting and legitimate, however secret, marriage to her superintendent enables her to create a space of intimate utopia where the couple is free from these alienating passions and humours. Yet, the dystopian antiquated world of melancholy passions destroys her new way of loving as the Duchess is persecuted by her brothers whose only will is revenge. Her act of dying makes vain the very predication on vanity that Bosola tries to implement to please her brothers. Because of its beautiful simplicity, her death enacts a modern form of aesthetics, that of the sublime.